Evaluating the effects of climate change and biotic interactions on terrestrial ectotherms through time and space - Tarr, Simon (2020)
Understanding the limits to species ranges and distributions remains a difficult and long-standing problem in the field of macroecology. This difficulty exists because species’ range limits reflect several complex and interacting processes including; physiological responses to abiotic conditions, biotic interactions and species’ dispersal abilities across geographic space. This complexity is increased further under rapid anthropogenic climate change which is predicted to affect all these processes simultaneously. Nonetheless, recent advances in species distribution modelling—particularly mechanistic species distribution models which can estimate a species’ fundamental niche—have provided novel means to further understand how species distributions manifest across large geographic extents. Despite these methodological breakthroughs, there remain substantial gaps in our knowledge of species’ distributions including: (1) How does climate alter the spatial distribution of ectotherm activity budgets through time and space? (2) What are the relative contributions of biotic interactions, dispersal ability and availability of preferred habitat type in limiting species’ ranges across geographic space? and (3) Does climate generate repeatable and predictable patterns of biodiversity? Here—within a species distribution modelling framework—I use both correlative and mechanistic species distribution models to address these questions. I reveal how climate, biotic interactions and species’ dispersal abilities limit ranges across large spatial extents and that by integrating correlative and mechanistic species distribution models we may tackle questions that have, until very recently, been out of reach. I predict that over the next decade macroecology will witness an increased use of correlative and mechanistic models in tandem to leverage the strengths of both approaches. Despite continued anthropogenic pressures on species across the globe limiting where species can survive, it is nonetheless an exciting time to be working in the field of macroecology and species distribution modelling.